ANALYSIS OF THE AGRO-INDUSTRIAL COMPLEX OF CRIMEA: FOOD SECURITY OF THE REGION - Viktor Reutov; Mir Abdul Kayum Jallal; Oleg Sviridov; Olga Korobeynikova; Oleg Blazhevich; Aleksandr Bondar; Shakizada Niyazbekova; Kamyshova Anna Borisovna (Scientific Journal of Pedagogy and Economics, 2021)
The study of the system of relations between participants in agricultural relations that ensures active quality reproduction processes and profitability of activities, reduces internal and external risks and threats to business and guarantees food security of the municipality, the region and the country as a whole. Goal. To analyze the agro-industrial complex of the Republic of Crimea as a component of the region’s industrial safety. The hypothesis of the study. Agricultural producers are gradually adapting to the new conditions in the Republic of Crimea during 2014-2017, and there are some problems in the production of agricultural products. Method or methodology of the work. The authors used structural-logical sequence of analysis of indicators of agro-industrial complex, considering the General characteristics of agro-industrial complex of the Republic of Crimea, the structure of the agricultural products of the Crimea, advanced agricultural enterprises. Using a structural-logical sequence of analysis of indicators of agro-industrial complex, it can be noted that, in general, the agricultural potential of Crimea is huge, however, the instability of some components, at the end of 2017, a decline, a decrease in the rate of growth of crop, livestock, thus we see the net profit and increased share of profitable enterprises. This dynamics suggests that agricultural producers are gradually adapting to new conditions, but there are some problems that hinder more fruitful development, primarily in terms of resource provision, logistics aspects and technological upgrades. The strategy for the development of the agro-industrial complex of the Republic of Crimea, as a component of the region’s industrial security – is to create safe conditions for development, improve the quality and volume of agricultural production, and its competitiveness in the Republic of Crimea. The scope of the results. The results obtained are of practical significance and can be used by economic entities in the agricultural industry, implementation of investment projects at the level of the Republic of Crimea. Further research should be directed to the development of methods for assessing the economic security of the agro-industrial complex with the choice of indicators proposed in this study as a component of economic security.